2021
DOI: 10.5194/amt-14-5593-2021
|View full text |Cite
|
Sign up to set email alerts
|

High-temporal-resolution wet delay gradients estimated from multi-GNSS and microwave radiometer observations

Abstract: Abstract. We have used 1 year of multi-GNSS observations at the Onsala Space Observatory on the Swedish west coast to estimate the linear horizontal gradients in the wet propagation delay. The estimated gradients are compared to the corresponding ones from a microwave radiometer. We have investigated different temporal resolutions from 5 min to 1 d. Relative to the GPS-only solution and using an elevation cutoff angle of 10∘ and a temporal resolution of 5 min, the improvement obtained for the solution using GP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…[11] used different software packages and compared the differences in the estimated tropospheric gradients for several stations on an island in the Mediterranean Sea. Recently, the quality of tropospheric gradients with high temporal resolution has been assessed by comparison to independent measurements such as a microwave radiometer [12]. To this end, the studies were limited to a handful of stations.…”
Section: Introductionmentioning
confidence: 99%
“…[11] used different software packages and compared the differences in the estimated tropospheric gradients for several stations on an island in the Mediterranean Sea. Recently, the quality of tropospheric gradients with high temporal resolution has been assessed by comparison to independent measurements such as a microwave radiometer [12]. To this end, the studies were limited to a handful of stations.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to further understand the relationship of the tropospheric gradients with the atmospheric variables and to what extent they can be used to nowcast, or even forecast, of weather events. Moreover, recent research on the short term gradients has been pursued [16] to detect short-lived gradients, and it has been found that the weaker the constraint on the stochastic processes that tailors the variance on the horizontal tropospheric gradients, the better those estimates can be tracked. The choice of temporal resolution is a compromise between getting a high correlation and the possibility of detecting rapid changes in the gradient.…”
Section: Introductionmentioning
confidence: 99%
“…However, a spatial and temporal resolution of the radiosonde measurements is the biggest limitation in the verification of the much denser and more frequently acquired GNSS products. The microwave radiometers are used in verification of the GNSS humidity estimates with a standard resolution of 1 hour (Lu et al, 2016); first attempts of a high temporal resolution comparisons (5 minutes) have been made by Ning and Elgered, (2021). The studies show agreement between PWV measured by WVR and GNSS estimates at the level of 1-4 mm (Ohtani and Naito, 2000;Liou et al, 2001;Dai et al, 2002).…”
Section: Introductionmentioning
confidence: 99%